2010
DOI: 10.1007/s00380-010-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

Heart valve surgery in octogenarians: operative and long-term results

Abstract: This study was performed to evaluate surgical outcomes in octogenarian patients undergoing valve surgery. Sixty patients (mean age 82.3 ± 1.9 years) who underwent valve surgery were reviewed. Aortic valve disease was found in 65% of the patients. Preoperatively, 20% of the patients were in NYHA class IV. An urgent operation and concomitant coronary artery bypass grafting were performed in ten patients each. A bioprosthetic valve was exclusively used for valve replacement except in two patients. Mitral valve re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 16 publications
0
22
3
Order By: Relevance
“…However, the postoperative outcome in group Idid not significantly differ from those reported by other authors [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussioncontrasting
confidence: 70%
“…However, the postoperative outcome in group Idid not significantly differ from those reported by other authors [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussioncontrasting
confidence: 70%
“…3) Aoyagi et al studied 60 octogenarians undergoing heart valve surgery and reported that urgent operation, preoperative NYHA class IV, preoperative renal dysfunction, perioperative use of an intra-aortic balloon pump, and prolonged cardiopulmonary bypass had an influence onoperative mortality. 9) While the present study suggested that the indications for surgery should not be determined by age alone, severe CKD was found to be a strong contraindication with a 6-month mortality rate of 57.1%. Thus, TAVI should probably be considered for dialysis patients although it is not indicated for these patients at present.…”
Section: Discussioncontrasting
confidence: 54%
“…6) transcatheter aortic valve replacement (TAVR) proved this new approach as an effective, alternative treatment to conventional SAVR in selected patient populations. 7,8) An evaluation of outcomes after SAVR in high-risk surgical patients is required in order to identify the best option for each patient population.…”
Section: Introductionmentioning
confidence: 99%